Antara Stabilisasi dan Ketergantungan: Mengevaluasi Efektivitas MINUSTAH di Haiti - Salsabila Aulia Irawan (Journal of Peace, Security and Democracy, 2026)
This study analyzes the effectiveness of the United Nations Stabilization Mission in Haiti (MINUSTAH) in addressing the security crisis and supporting state-building in Haiti, a fragile country. Using a qualitative approach based on literature, this study examines three main dimensions: security stabilization, political stability, and institutional capacity. The results show that MINUSTAH succeeded in reducing violence and supporting elections, thus creating short-term stability. However, this success was temporary and highly dependent on the presence of international actors. In the long term, MINUSTAH has not been able to strengthen institutional capacity sustainably and has tended to increase dependence on external aid. Furthermore, various criticisms such as human rights violations, the cholera scandal, and a legitimacy crisis have also affected the intervention's effectiveness. This study concludes that international intervention was effective in initial stabilization but limited in creating independent and sustainable state-building.